EXERGAMES LAB: A COMPLEMENTARY SPACE FOR PHYSICAL EDUCATION CLASSES - Finco, Mateus David (2015)
This paper presents a study about the use of exergames in structured Physical Education (PE) classes with students that usually show signs of dissatisfaction with sports activities proposed at regular PE classes. While videogames have been historically associated with issues related to obesity and social introversion, exergames brought a new perspective on those cultural artifacts. Twenty-four 8-14-year-old students participated in the study conducted in a laboratory set up in a school in Southern Brazil. They were observed and their PE teachers were also interviewed at the end of project. Results showed that students that usually did not show interest in Physical Education classes started to demonstrate a positive attitude regarding exergame practices, also expressing willingness to cooperate with their peers.